EFFECT OF COMBINATION OF AMIODARONE AND BETA-BLOCKERS ON THE CLINICAL PRESENTATION OF ATRIAL FIBRILLATION DEPENDING ON THE DURATION OF THE QTc - Kulyk, V. L. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
In 64 patients (41 males and 23 females) aged (65 ± 12) years with atrial fibrillation (AF) studied the effect of a combination of amiodarone and beta-blockers (BB) on the clinical signs of AF depending on the duration of the QTc. As a result of therapy in patients with AF in a subgroup of normal QTc observed more significant decrease of functional class of heart failure and stable angina, the degree of hypertension, reduced frequency of ventricular contractions, and systolic and diastolic blood pressure, improving the pumping function heart than in the subgroup of long QTc. Tendency to further increase of the initially prolonged QTc interval duration with therapy of amiodarone and BB combination requires strict control in such patients.